Research of LDPC decoding based on LLR BP algorithm - Sun Zengyou; Zhang Jin; Du Juan (2011 Cross Strait Triple-Regional Radio Science and Wireless Technology Conference, 2011)
In iterations processing of LLR BP algorithm for LDPC decoding, the computational complexity of check nodes renewal is high; The decoding performance will be reduced, while there are lots of loops in short LDPC codes. According to these problems, a new LLR BP decoding algorithm based on Hybrid Check-Variable offset processing is proposed in this paper. Decrease complexity by adjusting amplitudes of check nodes processing and relativity of variable nodes by adjusting their information. Simulation results show that this improved decoding algorithm, compared with LLR BP algorithm, is consideration to decoding performance of LDPC and computational complexity.